Estimation of the Demand for Urban Housing Services from Household Interview Data - Straszheim, Mahlon R. (The Review of Economics and Statistics, 1973)
THIS ANALYSIS EXTENDS THE CONVENTIONAL MODEL OF HOUSING CHOICE, DEFINING HOUSING AS A MULTIDIMENSIONAL COMMODITY WITH SEVERAL QUALITY ATTRIBUTES WHOSE PRICES VARY THROUGHOUT THE CITY IN A DISCONTINUOUS FASHION. WORK SITE AND ACCESSIBILITY HAVE SIGNIFICANT EFFECTS ON HOUSEHOLDS' CHOICE OF A LOCATION AND THE AMOUNT OF HOUSING CONSUMED. DESPITE HOUSEHOLDS' WILLINGNESS TO ALTER THEIR WORK TRIP WHEN CONFRONTING DIFFERENT PRICES, RESIDENTIAL LOCATION CHOICES ARE SIGNIFICANTLY AFFECTED BY THE SPATIAL DISTRIBUTION OF EMPLOYMENT. /DOT/